2013
DOI: 10.1111/1574-6941.12252
|View full text |Cite
|
Sign up to set email alerts
|

Volatiles produced by the mycophagous soil bacteriumCollimonas

Abstract: It is increasingly recognized that volatile organic compounds play an import role during interactions between soil microorganisms. Here, we examined the possible involvement of volatiles in the interaction of Collimonas bacteria with soil fungi. The genus Collimonas is known for its ability to grow at the expense of living fungi (mycophagy), and antifungal volatiles may contribute to the attack of fungi by these bacteria. We analyzed the composition of volatiles produced by Collimonas on agar under different n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
151
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(158 citation statements)
references
References 37 publications
6
151
0
1
Order By: Relevance
“…Furthermore, exposure to bacterial volatiles has been reported to change fungal morphology, enzyme activity and gene expression (Wheatley, 2002;Vespermann et al, 2007;Minerdi et al, 2008Minerdi et al, , 2009Kai et al, 2009;Garbeva et al, 2011Garbeva et al, , 2014b. For example, activity of laccases and tyrosinases can be strongly affected by bacterial volatiles (Wheatley, 2002).…”
Section: Volatile-mediated Antifungal Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, exposure to bacterial volatiles has been reported to change fungal morphology, enzyme activity and gene expression (Wheatley, 2002;Vespermann et al, 2007;Minerdi et al, 2008Minerdi et al, , 2009Kai et al, 2009;Garbeva et al, 2011Garbeva et al, , 2014b. For example, activity of laccases and tyrosinases can be strongly affected by bacterial volatiles (Wheatley, 2002).…”
Section: Volatile-mediated Antifungal Activitymentioning
confidence: 99%
“…Sensitivity to volatiles can strongly differ between fungal species and the extent of inhibition depends on the individual bacteria-fungus or fungus-fungus interaction (Kai et al, , 2009Vespermann et al, 2007;Garbeva et al, 2014b). Several independent studies have reported that F. solani is not much affected by bacterial volatiles, whereas Pythium species (oomycetes) are highly sensitive to bacterial volatiles (Kai et al, 2009;Effmert et al, 2012;Garbeva et al, 2014a,b).…”
Section: Volatile-mediated Antifungal Activitymentioning
confidence: 99%
“…The high abundance of sulfur containing volatiles in this study can be related to the cultivation of the tested bacteria on 1/10 th TSBA growth media. Several studies indicated that the composition of the volatile blend greatly depends on the growth media composition and the growth conditions (Schulz et al, 2004;Schulz and Dickschat, 2007;Blom et al, 2011;Garbeva et al, 2014b). The high amount of dimethyl di-and trisulfide detected in both monocultures and interactions indicate that these compounds are commonly produced.…”
Section: Discussionmentioning
confidence: 99%
“…The high amount of dimethyl di-and trisulfide detected in both monocultures and interactions indicate that these compounds are commonly produced. Many studies have shown that bacterial volatiles play a major role in soil fungistasis (Zou et al, 2007;Garbeva et al, 2011a;Garbeva et al, 2014b;van Agtmaal et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation